Manajemen Pembelajaran Guru Mata Pelajaran IPS SD.Kecamatan Rappocini Kota Makassar - Muchtar, Fitri Yanty (Universitas Negeri Makassar, 2018)
The objective of this research is to know the role of principal in the management of teacher learning in the subjects of IPS SD and the management of teacher learning in the subjects of IPS SD. The type of research is qualitative descriptive and place of research in elementary school subdistrict of Rappocini city of Makassar. Data collection is done by observation, interview, and documentation with analysis technique through data reduction, data display, and simultaneous data verification. The results show that in the learning management in primary school the principal acts as education, manager, administrator, supervisor, leader, innovator, motivator and entrepreneur. The principal plays an important role in mobilizing teachers in optimizing their function as managers in the classroom. As the principal in teacher learning management in this case planning supervision on teacher performance starting from learning management planning of IPS, implementation of learning, supervision of evaluation and follow up. The teacher acts as a manager in a class that is responsible for managing learning and learning outcomes. The learning management of IPS subjects includes planning, organizing, controlling (guiding) activities and evaluating activities related to the learning process of students. The management of teachers in IPS lessons runs the curriculum, IPS learning syllabus, learning implementation plan, method, IPS learning strategy, and evaluation of social studies and teaching materials